2008
DOI: 10.1038/sj.bjc.6604230
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral oestrogen in the treatment of prostate cancer: a systematic review

Abstract: The objectives of this study were to assess the effectiveness and safety of parenteral oestrogen in the treatment of prostate cancer, and to examine any dose relationship. A systematic review was undertaken. Electronic databases, published paper and internet resources were searched to locate published and unpublished studies with no restriction by language or publication date. Studies included were randomised controlled trials of parenteral oestrogen in patients with prostate cancer; other study designs were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…The trials differed with regard to the included patients, formulation and dose of parenteral estrogen, comparator used, outcome measures reported, and the duration of follow-up. The results provide no evidence to suggest that parenteral estrogen is consistently associated with an increase in cardiovascular mortality compare with orchidectomy or LHRHa (34).…”
Section: Effects Of Cross-sex Hormone Treatment On Cardiovascular Heamentioning
confidence: 58%
“…The trials differed with regard to the included patients, formulation and dose of parenteral estrogen, comparator used, outcome measures reported, and the duration of follow-up. The results provide no evidence to suggest that parenteral estrogen is consistently associated with an increase in cardiovascular mortality compare with orchidectomy or LHRHa (34).…”
Section: Effects Of Cross-sex Hormone Treatment On Cardiovascular Heamentioning
confidence: 58%
“…Overall experience with the therapeutic use of estrogens in PCa does not suggest a clinically important pro-carcinogenic effect. A systematic review of 20 RCTs of the use of high-dose parenteral E 2 as ADT for locally advanced or metastatic PCa found no evidence that E 2 treatment differed in efficacy from LHRHa or orchiectomy when comparing overall mortality (Norman et al 2008). Oncologic outcomes from the PATCH study are yet to be reported (Langley et al 2013).…”
Section: Effects Of Estradiol On Prostate Cancermentioning
confidence: 99%
“…For symptomatic breast enlargement requiring intervention, the proportions were 9% and 0%, respectively. Pre-treatment breast irradiation, given as a single dose, has efficacy in preventing gynaecomastia and was part of older protocols for oral DES (Beck et al 1978) and intramuscular PEP (Norman et al 2008). In SPCG-5, 240 mg intramuscular PEP per month over 11 years caused gynaecomastia in the majority of patients: 60% of those who received prophylactic breast irradiation and 84% of those who did not (by comparison, 48% of irradiated and 36% non-irradiated patients in the CAB group) (Hedlund et al 2008).…”
Section: Gynaecomastiamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly,arecentsystematicreviewprovidednoevidence that parenteral estrogen, in doses sufficient to produce castrate levels of testosterone, is less effective than LHRH or orchidectomyincontrollingprostatecancer,orthatitisconsistently associated with an increase in cardiovascular mortality [8].Somestudiesinvestigatedtheroleofantiandrogen monotherapy in non-metastatic prostate cancer [9][10]. The analysisoftherandomizedEarlyProstateCancerPrograminvestigatingtheadditionofbicalutamide,150mg,tostandard careforlocalizedorlocallyadvancednon-metastaticprostate cancer(medianfollow-up7.4years)hasshownthatantiandrogendoesnotbenefitpatientswithlocalizeddiseasebutdoes confersignificantprogression-freesurvivalbenefitsinlocally advanced disease, irrespective of the standard care received (radicalprostatectomy,RT,orwatchfulwaiting) [9].…”
Section: Adjuvant Hormonal Therapymentioning
confidence: 99%